THE CRIMINALISATION OF CORRUPTION OF PUBLIC OFFICIALS AS A MECHANISM FOR THE PROTECTION OF THE EUROPEAN UNION’S FINANCIAL INTERESTS (REVISTA PARADIGMA, 2020)
This paper is aimedat studying the process of Europeanisation of the fight against corruption through criminal law as a mechanism for the protection of the financial interests (PIF) of the European Union. The criminalisation of corruption is an obligation imposed to Member States by the PIF Directive. Additionally, the paper explores the challenges faced by Member States in the transposition of the PIF Directive and the interlink with the implementation of the EPPORegulation (European Public Prosecutor’s Office). The article concludes that the PIF Directive constitutes a progress in a comprehensive strategy for the protection of the Union’s financial interests as it foresees several provisions concerning harmonisation of criminal law measures, but the complete harmonisation is still far to be achieved since the PIF Directive leaves a wide leeway to Member States concerningissues such as the criminal sanctions and the limitation periods. The EPPO will clearly contribute to improve the EU strategy against corruption and other conducts affecting the EU budget, but a number of problems may arise due to the diverse legislations in the Member States.